Suitable multicomponent organic synthesis using heteropolycompounds as catalysts - Sanchez, Laura Mabel (2015)
Nowadays, scientists need to work with non-contaminating technologies. Some approaches include the use of multicomponent reactions (MCRs), and solid and reusable catalysts. Through MCRs it is possible to work without isolating intermediate products, so the use of auxiliary solvents is minimized. Furthermore, catalysis by heteropolycompounds is a field of increasing importance worldwide. Heteropolycompounds are effective, reusable and stable solid catalysts that have intrinsic multifunctionality: they can be designed in order to enhance their redox or superacidic properties by varying the atoms in their formula. The present review presents recent advances in the synthesis of organic compounds through multicomponent reactions by using heteropolycompounds as catalysts. Some of these compounds are: dihydropyrimidinones, quinazolinones, naphthol derivatives, pyridines, xanthenones, azabicyclo[2.2.2]octan-5-ones, dispiroheterocycles, imidazoles, spirofused heterocycles, and 1,4-dihydropyridines.